1969
DOI: 10.1055/s-0028-1098086
|View full text |Cite
|
Sign up to set email alerts
|

An Endoscopic Recognition of the Atrophic Border and its Significance in Chronic Gastritis

Abstract: The endoscopic atrophic border is a boundary between the pyloric and fundic gland territories, which is endoscopically recognized by discriminating differences in color and height of the gastric mucosa. The existence of superficial gastritis might exag-gerate the color and niveau differences, thus making it much easier to recognize the atrophic border. And also, according to the results of precise biopsy taken perpendicularly across the endoscopic atrophic border, it might be the boundary of histological atrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
856
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 900 publications
(876 citation statements)
references
References 0 publications
11
856
2
7
Order By: Relevance
“…The size of the diaphragmatic hiatus was assessed during endoscopic observation by comparing the width of the cardiac opening with the diameter of the shaft used for endoscopy at the cardiac portion and divided into three categories (<1.0, 1.0-2.0, >2.0 cm). The degree of gastric mucosal atrophy was endoscopically evaluated using the classification of Kimura and Takemoto, by which gastric mucosal atrophy was divided into six groups (C1, C2, C3, O1, O2, O3) (25). It has been shown that gastric acid secretion in patients with gastric mucosal atrophy decreases successively from C1 to O3 (26).…”
Section: Introductionmentioning
confidence: 99%
“…The size of the diaphragmatic hiatus was assessed during endoscopic observation by comparing the width of the cardiac opening with the diameter of the shaft used for endoscopy at the cardiac portion and divided into three categories (<1.0, 1.0-2.0, >2.0 cm). The degree of gastric mucosal atrophy was endoscopically evaluated using the classification of Kimura and Takemoto, by which gastric mucosal atrophy was divided into six groups (C1, C2, C3, O1, O2, O3) (25). It has been shown that gastric acid secretion in patients with gastric mucosal atrophy decreases successively from C1 to O3 (26).…”
Section: Introductionmentioning
confidence: 99%
“…Mapping studies of biopsy findings suggested that chronic atrophic gastritis develops from the lesser curvature of the lower gastric body and extends upward and laterally in the corpus. 13 Furthermore, the presence of IM in the lesser curvature of the corpus had the strongest association with cancer risk. 14 Form these observations, 5,6,14 we can easily understand that specific endoscopic findings well matched with IM and atrophic gastritis can be a great help to understand the high-risk group without multiple biopsies.…”
Section: Atrophic Gastritis As a Pre-neoplastic Conditionmentioning
confidence: 95%
“…4). 13 The gastric mucosa on the border itself and on the fundic gland side has neutrophil and mononuclear cell infiltration but no atrophy or IM. By contrast, on the pyloric side of the border, the mucosa shows atrophy of the fundic glands with or without IM.…”
Section: Atrophic Gastritis In Conventional White Light Imagementioning
confidence: 99%
See 2 more Smart Citations